Stabilization of linear nonautonomous systems with norm-bounded controls - V. N. Phat (2018)
In this paper, we study the stabilization problem for a class of linear nonautonomous systems with norm-bounded controls. Using the Lyapunov function technique, we establish simple verifiable stabilizability conditions without solving any Riccati differential equation. Numerical examples are given to illustrate the results. © 2006 Springer Science+Business Media, Inc.